2017
DOI: 10.1038/srep44411
|View full text |Cite
|
Sign up to set email alerts
|

Electrospun Nb-doped TiO2 nanofiber support for Pt nanoparticles with high electrocatalytic activity and durability

Abstract: This study explores a facile method to prepare an efficient and durable support for Pt catalyst of polymer electrolyte membrane fuel cell (PEMFC). As a candidate, Nb-doped TiO2 (Nb-TiO2) nanofibers are simply fabricated using an electrospinning technique, followed by a heat treatment. Doping Nb into the TiO2 nanofibers leads to a drastic increase in electrical conductivity with doping level of up to 25 at. % (Nb0.25Ti0.75O2). Pt nanoparticles are synthesized on the prepared 25 at. % Nb-doped TiO2-nanofibers (P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(38 citation statements)
references
References 36 publications
0
35
0
Order By: Relevance
“…Compared to hydrogen-oxidation fuel cells, direct alcohol fuel cells (DAFCs) exhibited many advantages; namely, high conversion efficiency, high power density, and readily storage as well as facile transportation 1 . Up to now, carbon-supported Pt catalysts have widely utilized for both anode and cathode 2 , however, electrochemical corrosion of the carbon support 3 causes the dissolution/detachment, Ostwald ripening, aggregation 4,5 of the Pt nanocatalysts and thus the fuel cell performance is drastically deteriorated in long-term operation. In view of the above issues, numerous efforts have been devoted to designing non-carbon catalyst supports, which possess high corrosion resistance and strong interplay with the Pt nanocatalyst.…”
Section: Introductionmentioning
confidence: 99%
“…Compared to hydrogen-oxidation fuel cells, direct alcohol fuel cells (DAFCs) exhibited many advantages; namely, high conversion efficiency, high power density, and readily storage as well as facile transportation 1 . Up to now, carbon-supported Pt catalysts have widely utilized for both anode and cathode 2 , however, electrochemical corrosion of the carbon support 3 causes the dissolution/detachment, Ostwald ripening, aggregation 4,5 of the Pt nanocatalysts and thus the fuel cell performance is drastically deteriorated in long-term operation. In view of the above issues, numerous efforts have been devoted to designing non-carbon catalyst supports, which possess high corrosion resistance and strong interplay with the Pt nanocatalyst.…”
Section: Introductionmentioning
confidence: 99%
“…Electrospinning is a simple but versatile technique for fabricating micro/nanofibers, and both single fibers and entangled fibrillar scaffolds have been extensively exploited for energy storage devices 1 , 2 , sensors 3 , 4 , and biomedical applications 5 9 . Beside the relative simplicity and scalability in fabrication, one common reason for its popularity is that electrospun fibers exhibit large porosity as well as high surface area-to-volume ratio, which are not straightforward to generate by other conventional bottom-up or top-down fabrication methods.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, cationic/anionic doping (such as Nb and N) and oxygen vacancy defects are demonstrated to be the most effective strategies for altering the physicochemical properties of TiO 2 . [218,221,222] For example, Kim et al [222] reported electrospun Nb-doped TiO 2 nanofibers with increased electrical conductivity. When Pt nanoparticles were loaded on Nb-doped TiO 2 nanofibers, the as-prepared Pt/Nb-TiO 2 nanofiber catalyst exhibited similar ORR activity to Pt/C in 0.1 m HClO 4 .…”
Section: Oxides Nanofibersmentioning
confidence: 99%